For Public Sociology - Burawoy, Michael (American Sociological Review, 2005)
Responding to the growing gap between the sociological ethos and the world we study, the challenge of public sociology is to engage multiple publics in multiple ways. These public sociologies should not be left out in the cold, but brought into the framework of our discipline. In this way we make public sociology a visible and legitimate enterprise, and, thereby, invigorate the discipline as a whole. Accordingly, if we map out the division of sociological labor, we discover antagonistic interdependence among four types of knowledge: professional, critical, policy, and public. In the best of all worlds the flourishing of each type of sociology is a condition for the flourishing of all, but they can just as easily assume pathological forms or become victims of exclusion and subordination. This field of power beckons us to explore the relations among the four types of sociology as they vary historically and nationally, and as they provide the template for divergent individual careers. Finally, comparing disciplines points to the umbilical chord that connects sociology to the world of publics, underlining sociology's particular investment in the defense of civil society, itself beleaguered by the encroachment of markets and states.